Infectious diseases and agriculture - Grace, Delia (Elsevier, 2019)
Agriculture has huge impacts on human health, both positive and negative. Agriculture has not been oriented to achieving health outcomes. The livestock sector creates a disproportionate share of risks and benefits. Health problems related to farming and food require solutions that include these sectors.